The clue of the broken blade - Dixon, Franklin W. (Grosset & Dunlap, 1970)
While searching for the guard end of a broken saber that will solve one mystery, the Hardy brothers become involved with a gang of bank robbers.
While searching for the guard end of a broken saber that will solve one mystery, the Hardy brothers become involved with a gang of bank robbers.
Donated by Patricia Bravender.
Keywords: Adventure stories. / http://id.loc.gov/authorities/subjects/sh85001072; Detective and mystery stories. / http://id.loc.gov/authorities/subjects/sh85037260; Hardy Boys (Fictitious characters) / Juvenile fiction.; Fencing / Juvenile fiction.; Bank robberies / Juvenile fiction.